Strategy of the full gosprozrakhunku as a basis of economic stability and competitiveness of production (enterprise) - Krikun, K.; Oliferuk, S.; Ryazanov, A. (Ways to Improve Construction Efficiency, 2018)
The article deals with three types of economic relations of the enterprise. Definition of self-financing and self-financing. The schemes of the marketing system of management and marketing system of self-management by the enterprise are also shown.